Aquaculture policy: Designing licenses for environmental regulation. (April 2022) - Osmundsen, Tonje C.; Olsen, Marit Schei; Gauteplass, Asle; Asche, Frank
Abstract: Public regulation of a successful industry such as aquaculture needs to consider different concerns such as industry growth and development, but also environmental and societal sustainability. Governance systems are continuously challenged to respond in adequate manners to how aquaculture industry develops. This is especially noticeable when it comes to how environmental challenges are handled. In this article, we investigate three different environmental regulations, all which aim to promote the development of more environmentally friendly production technologies to curb the negative environmental impacts of salmon aquaculture. Based on earlier research, and an investigation of publicly available documents, we study the development processes and the ultimate design of the "green" licenses, the "development" licenses, and the "eco-technology" licenses. We find that the design of such licenses has changed considerable across the three schemes, but that the main contributions to regulation is to set the focus on environmental risks, and to give stimulus to technological innovation in fish farming. However, the side-effects are a large administrative burden and long-lasting award processes which at times have been characterized by lack of transparency and predictability.